Universidade neoliberal e governamentalidade: subjetividade de docentes do curso superior de administração na modalidade de educação a distância - Batista, Natalia Bousquet (2023)
The neoliberal context causes global economic, political, social and cultural transformations capable of modifying the dynamics of power and professional identities and, consequently, contemporary work relations. Reforms in neoliberal universities are aimed at valuing knowledge aligned with the market, profit maximization and the ideal of managerial control. In Brazil, education received a package of neoliberal measures after the 1990s and began a process of productive restructuring that expanded the role of the private sector in the sector and deregulated teaching activities. Considering the changes in education in the country, based on Michel Foucault's bipolitics studies, this thesis uses the concept of neoliberal governmentality in the broad sense, of the government of the populations, and in the strict sense, of the ethical exercise of self-government, to understand how Discourses from neoliberal universities (re)construct the professional identity of professors of higher education in administration who work in distance education in private higher education institutions and their relationships with changes in work in contemporary society. For this, a qualitative research was carried out, through in-depth interviews and documentary research. Subsequently, the data produced will be analyzed using the cartographic management technique. The understanding of power mechanisms that guide the processes of subjectivation of professors of the higher education course of administration working in the distance modality in private higher education institutions offered reflective elements of problematization of the status quo, in the exercise of a critical ontology of the government of us themselves, as researchers, inserting this work in an arena of resistance of academic practices against the effects of hegemonic discourse, based on critical reflection and the proposition of new ways of (re)existing in the face of asymmetries resulting from neoliberal premises.